The effect of the estimated innervation zone on EMG amplitude and center frequency - Beck, T. W.; Housh, T. J.; Cramer, J. T.; Weir, J. P. (Medicine & Science in Sports & Exercise, 2007)
Purpose: The purpose of this study was to examine the influence of electrode placement over the estimated innervation zone (IZ) for the vastus lateralis, as well as proximal and distal to the estimated IZ, on the isometric torque-related patterns for electromyographic (EMG) amplitude and mean power frequency (MPF).